Pemberian Asam Humat untuk Meningkatkan Pertumbuhan dan Kandungan Total Flavonoid Sawi Hijau (Brassica juncea L.) pada Perbedaan Kadar Salinitas - Tia Setiawati; Tentani Buhti Amadea; Mohamad Nurzaman; Nining Ratningsih (Jurnal Pro-Life, 2021)
Salt affects plant growth due to increased soil osmotic pressure and plant nutrients disturbance. Most plants are susceptible to high salinity which can cause physiological and biochemical interference. This research was conducted to obtain a possible salinity level for mustard greens (Brassica juncea L.) to grow well and the best humic acid dosage to reduce salinity damages and to gain high total flavonoid content. This research used Randomized Block Design method with two factors and four replications. The factors are salinity levels (control, 50, 75, and 100 mM) and humic acid dosage (control, 2, 4, and 8 g/kg). In the parameters which had interactions between the two treatments, the highest results were obtained with a combination of 100 mM salinity and 12 g humic acid, such as plant height (33.35 cm), leaf area (379.66 cm2), fresh weight (22.41 g) and dry weight (1.54 g). The highest results on leaf number (8.5 leaves) and total flavonoid content (0.074 mgQE/g sample) were obtained with 100 mM salinity. Humic acid dose of 12 g gave the highest result on leaf number (8.69 leaves) and total flavonoid content (0.095 mgQE/g sample).